Guided Growth in Leg Length Discrepancy in Beckwith-Wiedemann Syndrome: A Consecutive Case Series - Maurizio De Pellegrin; Lorenzo Brogioni; Guy Laskow; Graziano Barera; Roberta Pajno; Sara Osimani; Silvia Russo; Lorenzo Marcucci (Children, 2021)
Beckwith-Wiedemann Syndrome (BWS) is a rare genetic disorder characterized by overgrowth, macroglossia, abdominal wall defects, neonatal hypoglycemia, predisposition to embryonal tumor, lateralized overgrowth, and leg length discrepancy (LLD), which can affect normal posture and gait. Aim of this study was to evaluate the effects of guided growth (temporary epiphysiodesis technique) as LLD management in BWS patients. Between 2007 and 2021, 22 BWS patients (15 F, 7 M) with a mean age of 7.9 years (2.9–14.4) and a mean LLD at first surgery of 3.65 cm (2–10), underwent temporary proximal tibial (PTE) and distal femur epiphysiodesis (DFE). In 18 patients the first surgical procedure was PTE, in one, DFE, and in 3 cases, PTE and DFE at the same time, respectively. Eleven patients reached equality of leg length after a mean follow-up of 7.7 years (3.7–13.0) and mean age of 13.3 years (12.7–27.5); 10 patients underwent 3 surgical procedures, one 7 procedures. Fifteen patients had no complications. No severe complications, infection, articular stiffness, or neuro-vascular lesions occurred in remaining patients; complications included secondary varus or valgus axial deviation in a total of 6 patients, and two screw breakages in two patients. Guided growth as a minimally invasive procedure seems efficient for LLD treatment with low complication rate in BWS patients.